Modular Implementation of Neural network Structures in Marketing Domain Using Data Mining Technique (International Journal of Engineering and Computer Science, 2017)
The process of implementing neural networks comprises several strategies in the field of data mining. The proper application ofsupervised and unsupervised learning concepts play a vital role in the successful implementation of Neural network methodswhich are not easily used for data mining tasks. Since they often produce incomprehensible models and require long trainingtimes. In this paper we implement neural network learning algorithms that are able to produce comprehensible models and that donot require excessive training times. The real time implementation of marketing domain is taken into account for the incorporationof data mining rule extraction approach which involves extracting symbolic models from trained neural networks. In near futurewe will implement the descriptive and predictive approaches of data mining implementation in real time using neural networkconceptual schema.